Correction: Dietary Iodine Sufficiency and Moderate Insufficiency in the Lactating Mother and Nursing Infant: A Computational Perspective. - PLOS ONE Staff (PLoS ONE, 2016)
[This corrects the article DOI: 10.1371/journal.pone.0149300.].